Real estate collateral, lender screening, and M&A performance - Gao, Mingze; Luong, Thanh Son; Qiu, Buhui (Journal of Corporate Finance, 2026)
We study whether and how the market value of corporate real estate (REMV) shapes acquirer M&A performance. Using hand-collected loan agreements linked to M&A deals, we show that financing secured by real estate embeds tighter acquisition covenants and that, unlike other collateral, real estate collateral is associated with higher announcement returns. Instrumental-variables estimates based on headquarters-state property taxes, crime rates, and local natural-disaster exposure support a causal link from REMV to M&A deal performance. A two-by-two design crossing industry growth opportunities with acquisition covenants shows that both lender screening and financial flexibility mechanisms operate: returns are strongest when growth opportunities are high and covenants are restrictive, remain positive but smaller when only one channel is active, and vanish when both are weak. Consistent with ex-ante screening, acquirers borrowing against real estate are more likely to withdraw deals with negative announcement reactions. Our findings highlight the importance of real estate collateral in shaping corporate investment outcomes and suggest that real estate appreciation enhances firms' capacity to undertake more disciplined and value-creating acquisitions.